RETRACTED: Post-acute (long) COVID-19 quality of life: validation of the German version of (PAC19QoL) instrument - Umakanthan, Srikanth; Monice, Mariam; Mehboob, Salona; Jones, Cheryl Linda; Lawrence, Sam (Frontiers in Public Health, 2023)
Purpose: The aim of our study was to validate a German translation of the PAC‑19QoL instrument among German patients with long COVID-19 syndrome. Patients and methods: The PAC-19QoL instrument was translated into the German language and administrated to patients with long COVID-19 syndrome. Cronbach’s alpha coefficient was used to analyse the internal consistency of the instrument. Construction validity was evaluated by using Pearson’s correlation coefficient and Spearman’s rank correlation. Scores of patients and controls were compared using Mann-Whitney U test. Results: Forty-five asymptomatic and forty-one symptomatic participants were included. Forty-one patients with long COVID-19 syndrome completed the PAC-19QoL and EQ-5D-5L questionnaires. PAC-19QoL domain scores were significantly different between symptomatic and asymptomatic participants. All items achieved a Cronbach alpha greater than 0.7. There was a significant correlation between all domains on the test (p < 0.001), with the highest correlation of Total (r = 0.994) and Domain 1 (r = 0.991). Spearman’s rank correlation analysis confirmed that the instrument items correlated with the objective PAC-19QoL examination findings. Conclusion: The German version of the instrument is valid, reliable and can be a suitable tool for research and daily clinical practice among patients with long COVID-19 syndrome.